A roadmap for research in mobile business. (5th May 2005) - Fouskas, Konstantinos G.; Giaglis, George M.; Kourouthanassis, Panos E.; Karnouskos, Stamatis; Pitsillides, Andreas; Stylianou, Marinos
Mobile business research has arguably grown to become one of the most topical and complex eBusiness research areas in recent years. As a result, researchers face a plethora of interdisciplinary research challenges. Understanding the range of these challenges and confronting them requires coordinated research efforts, backed up by a holistic guiding approach. This paper aims at contributing to the future of mobile business research by proposing a roadmap to systematise and guide future research efforts, providing a methodical outlook to open research issues across all dimensions defining mobile business and prioritises future research in each dimension in the form of short-, medium-, and long-term research challenges.